Co-presenter, Co-Organiser - Christoforou, Maria (My University, 2026)
The members of the European Laboratory For Pedagogical Action Research And Student-Centred Learning (ELaRA) (3.4 action of EUt+) presented their research activity conducted during and in post-pandemic time. The establishment of collaborative opportunities among EUt+ partners was initiated.